2019
DOI: 10.1038/s41598-019-51447-8
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the temporal roaming behaviour of free-roaming domestic dogs in Indigenous communities in northern Australia to inform rabies incursion preparedness

Abstract: Australia is canine rabies free but free-roaming, domestic dog populations in remote northern communities are at risk of an incursion due to proximity to rabies-endemic south-east Asia. Unrestricted contact between dogs could facilitate rabies spread following an incursion, and increase the impact on both dogs and people. Whilst dog vaccination is the foundation of rabies prevention, control strategies could be enhanced by understanding the temporal pattern of roaming and associated risk factors, so that movem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 32 publications
2
26
2
Order By: Relevance
“…And attention to COVID-19, risk of infection and self-perceived health status were associated with higher levels of anxiety, depression, and stress. Respondents who felt that their lives were more severely affected by the COVID-19 exhibited more obvious anxiety, depression, and stress than the rest of them 26 . Specifically, we found that urban residents were more likely to report anxiety, depression and stress than rural counterparts.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…And attention to COVID-19, risk of infection and self-perceived health status were associated with higher levels of anxiety, depression, and stress. Respondents who felt that their lives were more severely affected by the COVID-19 exhibited more obvious anxiety, depression, and stress than the rest of them 26 . Specifically, we found that urban residents were more likely to report anxiety, depression and stress than rural counterparts.…”
Section: Discussionmentioning
confidence: 98%
“…Since respondents were those who had mobile phones with access to WeChat and decide to participate in the survey, which means that most people get information about COVID-19 mainly through the mass media. However, because our most investigations conducted in the early stage of shutdown, everyone had inadequate understanding of the actual situation of COVID-19, so discrimination and prejudice driven by fear or misinformation have been flowing globally 26 . Since people cannot differentiate true and false news, the more attention to COVID-19, the more unclear information may be received, which negatively affects respondents' psychological status.…”
Section: Discussionmentioning
confidence: 99%
“…Often, data were collected using Global Positioning System (GPS) tracking devices (1-4, 6-8, 11-16, 18-20), but other tools, such as capture-recapture (10,21) or interviews (9), were also used to collect data on FRDD roaming behavior. Home range (2,14,17,19), the area a dog commonly uses for normal activities, such as breeding or foraging, and distance from home (12,13,20) were applied to describe and investigate dog roaming behavior. These studies improved knowledge on FRDD behavior by investigating dog movements in relation to their habitat (15,16), interactions with wildlife (7,12), impact of dog characteristics (6,8,10,13,22), or sterilization (10,14) on dog roaming behavior.…”
Section: Introductionmentioning
confidence: 99%
“…However, dog behavior has also been investigated in regard to other dogtransmitted zoonotic diseases, such as echinococcosis (18,19), Leishmaniasis (25,26), or Rocky Mountain spotted fever (11), because of their impact on human health. The objectives of those studies include the refinement of current control strategies in endemic areas, preventing disease incursion in countries free from specific diseases (e.g., rabies in Australia) and informing dog population management programs (20,23,27).…”
Section: Introductionmentioning
confidence: 99%
“…In remote Indigenous communities in Northern Australia, most domestic dogs roam freely [ 15 , 16 ] and, therefore, can come into contact with dingoes. Hybridisation between dingoes and community-owned dogs in Northern Australia has been demonstrated [ 17 ].…”
Section: Introductionmentioning
confidence: 99%